Lessons in Self-Defense: Gender Violence, Racial Criminalization, and Anticarceral Feminism - Thuma, Emily (Women's Studies Quarterly, 2015)
Keywords: 1900-1999; 1980-1989; afro-féminisme; amériques; antiracisme; approches et analyses; cours; discipline; féminisme autochtone; féminismes noirs; histoire; injustice; intersectionnalité; militance; patriarcat; pol4212; premier cycle; périodes historiques; racisme; régions géographiques; résistance; sciences humaines; systèmes d'oppressions; thématiques; viol; violences; violences d'état; violences sexistes et sexuelles; états-unis; études de genres

Blanches et Noires : histoire(s) des Américaines au XIXe siècle - Lehuu, Isabelle (Cahiers de l'IREF, 2011)
«Les chapitres qui suivent mettent en lumière tant la parole des femmes que le discours sur les femmes, les actions et les représentations. Ils explorent la réalité quotidienne de femmes ordinaires du XIXe, jeunes et moins jeunes, mariées et célibataires, blanches et noires, au Nord comme au Sud, qui sont restées silencieuses, souvent dans l’ombre d’un mari, d’un père ou d’un maître. Leurs témoignages, les mots qu’elles ont laissés dans les sources publiques et privées, les gestes qu’elles ont posés aussi bien dans le cadre de leurs relations affectives qu’au sein de leur exploitation familiale, leur réseau social, leur travail, leur église, leur communauté urbaine ou villageoise, leur région, sont autant d’indices à décoder pour dresser un portrait nuancé et documenter la condition des femmes aux États-Unis dans toute sa diversité sociale et culturelle.»
Keywords: 1800-1899; afro-féminisme; amériques; approches et analyses; black feminism; cours; discipline; esclavagisme; femmes* blanches; femmes* noires; féminisme afroaméricain; féminismes noirs; his4443; histoire; histoire des femmes*; intersectionnalité; justice sociale; militance; mouvement aboitionnisme; philosophie politique; premier cycle; privilèges; périodes historiques; racisme; rapports sociaux de sexe; régions géographiques; sciences humaines; sciences sociales; sexisme; système colonial; systèmes d'oppressions; thématiques; violences; états-unis; états-unis (sud); études féministes

Unruly women: The politics of social and sexual control in the old South - Bynum, Victoria E. (Gender & American culture, 1992)
In this richly detailed and imaginatively researched study, Victoria Bynum investigates "unruly" women in central North Carolina before and during the Civil War. Analyzing the complex and interrelated impact of gender, race, class, and region on the lives of black and white women, she shows how their diverse experiences and behavior reflected and influenced the changing social order and political economy of the state and region. Her work expands our knowledge of black and white women by studying them outside the plantation setting.Bynum searched local and state court records, public documents, and manuscript collections to locate and document the lives of these otherwise ordinary, obscure women. Some appeared in court as abused, sometimes abusive, wives, as victims and sometimes perpetrators of violent assaults, or as participants in illicit, interracial relationships. During the Civil War, women frequently were cited for theft, trespassing, or rioting, usually in an effort to gain goods made scarce by war. Some women were charged with harboring evaders or deserters of the Confederacy, an act that reflected their conviction that the Confederacy was destroying them.These politically powerless unruly women threatened to disrupt the underlying social structure of the Old South, which depended upon the services and cooperation of all women. Bynum examines the effects of women's social and sexual behavior on the dominant society and shows the ways in which power flowed between the private and public spheres. Whether wives or unmarried, enslaved or free, women were active agents of the society's ordering and dissolution.
Keywords: 1800-1899; amériques; approches et analyses; civil war; cours; discipline; féminisme matérialiste; his4443; histoire; histoire des femmes*; histoire et politique; intersectionnalité; premier cycle; périodes historiques; racisme; rapports sociaux de sexe; ressource en ligne; régions géographiques; sciences humaines; sexualité; systèmes d'oppressions; thématiques; violences; états-unis